2016
DOI: 10.20882/adicciones.761
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedad, depresión y deshabituación tabáquica.

Abstract: Anxiety and depression showed significant and progressive improvement during treatment (A: baseline 9.2 ± 4.5, 5.9 ± 3.6 1 month, 3 months 4.5 ± 3.1, p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“… 44 54 55 A significant and progressive improvement of anxiety and depression was also reported in an observational study, and the protective effect was observed regardless of the presence of psychiatric pathology. 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 54 55 A significant and progressive improvement of anxiety and depression was also reported in an observational study, and the protective effect was observed regardless of the presence of psychiatric pathology. 49 …”
Section: Discussionmentioning
confidence: 99%
“…44 54 55 A significant and progressive improvement of anxiety and depression was also reported in an observational study, and the protective effect was observed regardless of the presence of psychiatric pathology. 49 Many studies demonstrated gender differences in varenicline efficacy for smoking cessation 56 57 ; some studies also found a difference in neuropsychiatric events between genders. 58 In this study, we found less risk of NPAEs by varenicline for females in the psychiatric cohort compared with NRT.…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…El uso del tabaco en población joven es una práctica que comienza a realizarse con un carácter más social y, durante la pandemia, su uso se tendió a cronificarse de forma individual (53,3% de nuestra muestra aumentó el consumo de tabaco). En el caso de la población adolescente, la asociación de reducir la ansiedad con el tabaco es considerada uno de los principales factores de riesgo y de adicción (Almadana et al, 2017). La ausencia de una rutina durante la cuarentena y la alteración de los horarios supuso desórdenes mentales que influyeron en su uso (Altena, et al, 2020).…”
Section: Me Ha Ayudado La Marihuana a Relajarme Los Días Que No Se Po...unclassified
“…However, other authors did not find significant differences between patients with high anxiety and/ or depression levels who quit smoking and general population. In addition, they describe that anxiety and depression levels decrease in the follow up when they quit the habit, regardless of the existence of psychopathology (Almadana, et al, 2016;Raich, et al, 2015).…”
Section: Extended Summarymentioning
confidence: 99%
“…Sin embargo, otros autores no encontraron diferencias significativas en los pacientes que dejan de fumar con altos niveles de ansiedad y/o depresión y la población general. Además, describen en sus seguimientos cómo estos niveles de ansiedad y depresión bajan tras el abandono del hábito, independientemente de la existencia de psicopatología (Almadana et al, 2016;Raich et al, 2015).…”
Section: Introductionunclassified